Gambaran Pengetahuan Perawat dalam Penerapan Asuhan Keperawatan Berbasis 3 S ( SDKI, SLKI DAN SIKI) - Miko Eka Putri; Mila Triana Sari; Fithriyani Fithriyani (Prosiding Seminar Kesehatan Nasional, 2025)
Nursing care service standards are inseparable from the nursing process which is the main task of nurses in providing nursing care. This process starts from assessment, establishing nursing diagnoses, preparing nursing care plans, implementing and evaluating the success of the care provided. Based on the results of interviews with 2 nurses, they said that they had been exposed to 3S-based nursing care standards. Therefore, it is necessary to identify the implementation of 3S-based nursing care (SDKI, SLKI, SIKI) at Putri Ayu Community Health Center. The purpose of this study was to determine the factors related to the implementation of 3S-based nursing care at Putri Ayu Community Health Center. Data collection was carried out on February 26, 2025. With a total sampling technique of 19 nurses. This study was conducted on February 12-22, 2024. With a total sampling technique of 19 nurses. Based on the results of the study, it shows that some respondents have sufficient knowledge (52.5%). Therefore, it is necessary to continuously improve nurses' knowledge regarding the implementation of the 3 Standards of Nursing Care